PELATIHAN TIME MANAGEMENT UNTUK STRES AKADEMIK SISWA - Febriani, Oki Kartika; Dewi, Fransisca Iriani Roesmala; Heng, Pamela Hendra (Universitas Islam Indonesia, 2024)
The burden of tasks and responsibilities without adequate time management skills can lead to academic stress in students. This study aims to determine the effectiveness of time management training on academic stress. The research design is experimental with a pretest and posttest control group design. The subjects were students with high academic stress, measured by the Educational Stress Scale for Adolescents (ESSA). The study involved 61 subjects, 33 in the control group and 28 in the experimental group, randomly assigned. The experimental group received 8 training sessions, while the control group received 1 session. Time management training included goal setting, prioritization, daily scheduling, stopping procrastination, effective time use, and assertiveness. The Wilcoxon paired group data analysis showed a p-value < 0.001, indicating that the intervention effectively reduced students' academic stress. The implication is that time management training can be developed as an effort to reduce academic stress in students.